Metformin in the Treatment of Amisulpride-Induced Hyperprolactinemia: A Clinical Trial - Zhu, Cuifang; Li, Ruofan; Ju, Mingliang; Xiao, Xudong; Yuan, Ti-Fei; Jin, Zhixing; Zhao, Jing (Frontiers in Molecular Neuroscience, 2022)
Objective To evaluate the efficacy and safety of metformin in the treatment of amisulpride-induced hyperprolactinemia. Methods A total of 86 schizophrenic patients who developed hyperprolactinemia after taking amisulpride were screened and randomly assigned to the metformin group (42 patients) and placebo group (44 patients) and followed up for eight weeks. The patients’ serum prolactin levels, blood glucose and lipids were measured at the baseline and the end of the intervention. The treatment emergent symptom scale (TESS) was also assessed. Results After eight weeks of intervention, serum prolactin levels in the metformin group decreased from (1737.360 ± 626.918) mIU/L at baseline to (1618.625 ± 640.865) mIU/L, whereas serum prolactin levels in the placebo group increased from (2676.470 ± 1269.234) mIU/L at baseline to (2860.933 ± 1317.376) mIU/L. There was a significant difference in prolactin changes (Fcovariance = 9.982, P = 0.002) between the two groups. There was no significant difference in the incidence of adverse drug reactions (P > 0.05) between the two groups. Conclusion Metformin is able to improve amisulpride-induced hyperprolactinemia with its safety.